69.4k views
2 votes
Find a solution to y'(t) = te^-t satisfying the condition y(1) = 1.

User Pescuma
by
5.7k points

1 Answer

4 votes

Answer:


y=-e^(-t)(t+1)+1+(2)/(e)

Explanation:

The given differential equation is


y'(t)=te^(-t)

It can be written as


(dy)/(dt)=te^(-t)


dy=te^(-t)dt

Integrate both sides.


\int dy=\int te^(-t)dt

Apply ILATE rule on right side. Here, t is first function and
e^(-t) is the second function.


y=t\int e^(-t)-\int ((d)/(dt)t\int e^(-t))


y=-te^(-t)-\int (1* (-e^(-t)))
\int e^(-x)=-e^(-x)+C


y=-te^(-t)+\int e^(-t)


y=-te^(-t)-e^(-t)+C .... (1)

Initial condition is y(1) = 1. It means at t=1 the value of y is 1.


1=-(1)e^(-t)-e^(-(1))+C


1=-e^(-1)-e^(-1)+C


1=-2e^(-1)+C


1=-(2)/(e)+C

Add
(2)/(e) on both sides.


1+(2)/(e)=C

Substitute the value of C in equation (1).


y=-te^(-t)-e^(-t)+1+(2)/(e)


y=-e^(-t)(t+1)+1+(2)/(e)

Therefore, the solution of given initial value problem is
y=-e^(-t)(t+1)+1+(2)/(e).

User Shivam Manswalia
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.